The hidden cost of the pool: environmental risk factors, clinical implications, strategies for prevention and treatment – a literature review - Chojnowska, Natalia; Kadłubowska, Karolina; Rytel, Jan; Sikorski, Adam; Szaryński, Mikołaj; Jakubowska, Paulina; Jakubowska, Martyna; Bursztyn, Michał; Bursztyn, Tomasz; Gólcz, Julia; et al. (Quality in Sport, 2025)
Dental erosion refers to the gradual loss of tooth structure caused by acids unrelated to bacteria. Competitive swimmers face a heightened risk due to frequent exposure to chlorinated pool water, often with low pH, which weakens enamel. This review compiles research from 2000 to 2025 on the prevalence, causes, symptoms, diagnosis, prevention, and treatment of enamel erosion in swimmers. Key risk factors include the duration of training, mouth breathing, and poor pool water maintenance. Saliva plays a vital role in protecting against erosion. Effective prevention strategies involve ensuring proper pool pH levels, using custom-fit mouthguards, and promoting good oral hygiene practices. Treatment options, depending on the severity, range from remineralization to restorative procedures. Despite growing awareness, regular dental check-ups among swimmers remain insufficient. An individualized, collaborative approach is crucial, along with enhanced education for both athletes and coaches. Routine monitoring should be integrated into sports dentistry practices to ensure long-term oral health.